2019
DOI: 10.2322/tjsass.62.310
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Vortex Lift in Low-Aspect-Ratio Wings at Very-low Reynolds Numbers

Abstract: The objective of this study is to ascertain the aerodynamic characteristics of low-aspect-ratio wings at Reynolds numbers ranging between 1©10 3 and 1©10 4 which correspond to insect wings. The wings tested in this study are rectangular, thin, flat plates with aspect ratios varying from 0.5 to 2. The very small forces and moment acting on the wings were measured using a low-pressure wind tunnel. Although a large maximum lift coefficient was obtained for the wing with an aspect ratio of 1 at a Reynolds number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…2016; Okamoto et al. 2019). Therefore, a thorough understanding of the structure and dynamics of separation bubbles is crucial to further improve the flight performance of MAVs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2016; Okamoto et al. 2019). Therefore, a thorough understanding of the structure and dynamics of separation bubbles is crucial to further improve the flight performance of MAVs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that wings with aspect ratios (A) exceeding approximately 1 commonly encounter separation bubbles in an angle-of-attack range α ≈ 4 • -10 • (Torres & Mueller 2001;Okamoto & Azuma 2011;Mizoguchi, Kajikawa & Itoh 2016). Meanwhile, in this α range, wings exhibit their maximum lift-to-drag ratio (Ananda, Sukumar & Selig 2015;Mizoguchi et al 2016;Okamoto et al 2019). Therefore, a thorough understanding of the structure and dynamics of separation bubbles is crucial to further improve the flight performance of MAVs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have established that the thin flat plate provides a higher lift-to-drag ratio at low Reynolds numbers, compared with the conventional thick aerofoil (McMasters & Henderson 1980;Mueller 1999). The effects of aspect ratio (AR) and planform shape on aerodynamic characteristics have been considered (Torres & Mueller 2001;Okamoto & Azuma 2011;Ananda, Sukumar & Selig 2015;Mizoguchi, Kajikawa & Itoh 2016;Okamoto et al 2019). It has been shown that wings with AR 1 exhibit the maximum lift-to-drag ratio within the angle of attack range α ≈ 4 • -10 • , regardless of the various planform shapes tested.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of aspect ratio () and planform shape on aerodynamic characteristics have been considered (Torres & Mueller 2001; Okamoto & Azuma 2011; Ananda, Sukumar & Selig 2015; Mizoguchi, Kajikawa & Itoh 2016; Okamoto et al. 2019). It has been shown that wings with exhibit the maximum lift-to-drag ratio within the angle of attack range , regardless of the various planform shapes tested.…”
Section: Introductionmentioning
confidence: 99%
“…Slender unswept wings can be used for various applications, ranging from missile control surfaces to more recent uses in small scale flight vehicles, i.e., drones and microaerial vehicles. As such, many studies have documented their performances [1][2][3][4][5][6][7][8][9]. These studies have shown that slender wings yield low lift curve slopes and low aerodynamic efficiency coupled with a delay in the stall angle compared to high aspect ratio wings.…”
Section: Introductionmentioning
confidence: 99%